How to be an Aztec warrior - Macdonald, Fiona, 1958- (How to be series., 2005)
Describes daily life in the Aztec empire and explains the skills and duties of Aztec warriors. Warriors needed, how would you like to join the team that defends your people and your homeland? Your main duties will include: defending your city against invaders, conquering new territory, controlling conquered peoples and collecting tribute from them, taking captives to sacrifice to the gods. How to join? Hurry to the main square of your city when you hear the beat of the big war drum. Offering a unique approach for young readers to interview for historical jobs, this new series sweeps readers back in time to show them what it took to be an Aztec warrior, a knight in the middle ages, a Roman soldier, and a samurai warrior in ancient Japan. Full color.